On the formulation of snow thermal conductivity in large-scale sea-ice models - Lecomte, Olivier; Fichefet, Thierry; Vancoppenolle, Martin; Domine, Florent; Mathiot, Pierre; Morin, Samuel; Barriat, Pierre-Yves; Massonnet, François; In Proceedings of the International Symposium on Sea Ice in a Changing Environment (2014)
An assessment of the performance of a state-of-the-art large-scale coupled sea-ice–ocean model, including a new snow multilayer thermodynamic scheme, is performed. Four 29 year long simulations are compared against each other and against sea-ice thickness and extent observations. Each simulation uses a separate parameterization for snow thermo–physical properties. The first simulation uses a constant thermal conductivity and prescribed density profiles. The second and third parameterizations use typical power-law relationships linking thermal conductivity directly to density (prescribed as in the first simulation). The fourth parameterization is newly developed and consists of a set of two linear equations relating the snow thermal conductivity and density to the mean seasonal wind speed. Results show that simulation 1 leads to a significant overestimation of the sea-ice thickness due to overestimated thermal conductivity, particularly in the Northern Hemisphere. Parameterizations 2 and 4 lead to a realistic simulation of the Arctic sea-ice mean state. Simulation 3 results in the underestimation of the sea-ice basal growth in both hemispheres, but is partly compensated by lateral growth and snow ice formation in the Southern Hemisphere. Finally, parameterization 4 improves the simulated snow depth distributions by including snow packing by wind, and shows potential for being used in future works. The intercomparison of all simulations suggests that the sea-ice model is more sensitive to the snow representation in the Arctic than it is in the Southern Ocean, where the sea-ice thickness is not driven by temperature profiles in the snow.